User-Centered Design in Pediatric Acute Care Settings Antimicrobial Stewardship - Ward, Michael J.; Chavis, Bryson; Banerjee, Ritu; Katz, Sophie; Anders, Shilo (Applied Clinical Informatics, 2021)
Background Antibiotic prescribing in ambulatory care centers is increasing. Previous research suggests that 20 to 50% of antibiotic prescriptions are either unnecessary or inappropriate. Unnecessary antibiotic consumption can harm patients by increasing antibiotic resistance and drug-associated toxicities, and the reasons for such use are multifactorial. Antimicrobial Stewardship Programs (ASP) were developed to guide better use of antibiotics. A core element of ASP is to provide feedback to clinical providers. To create clinically meaningful feedback, user-center design (UCD) is a robust approach to include end-users in the design process to improve systems.Objective The study aimed to take a UCD approach to developing antibiotic prescribing feedback through input from clinicians in two ambulatory care settings.Methods We conducted two group prototyping sessions with pediatric clinicians who practice in the emergency department and urgent care settings at a tertiary care children's hospital. Participants received background on the problem of antibiotic prescribing and then were interviewed about their information needs, perceived value, and desired incentives for a prescribing feedback system. Sessions concluded with their response and recommendations to sample sections of an antibiotic feedback report including orienting material, report detail, targeted education, and resources.Results A UCD approach was found to be highly valuable in the development of a feedback mechanism that is viewed as desirable by clinicians. Clinicians preferred interpreting the data themselves with aids such as diagrams and charts over the researcher concluded statements about the clinician's behavior. Specific feedback that clinicians considered redundant were removed from the model if preexisting alerts were established.Conclusion Integrating a UCD approach in developing ASP feedback identified desirable report characteristics that substantially modified preliminary wireframes for feedback. Future research will evaluate the clinical effectiveness of our feedback reports in outpatient settings.
Keywords: user-centered design; ambulatory care; antimicrobial stewardship programs; feedback; pediatrics; requirements analysis and design; qualitative